Smart Binder for construction worker at site - Alias , Siti Noor Asyikin; Bakri , Intan Zuriana; Afandi , Fawwaz Zuhaili (Jurnal Penyelidikan Sains Sosial, 2024)
The Smart Binder project seeks to enhance efficiency and quality in bricklaying processes for large-scale and medium-scale construction projects. Through the development and implementation of an innovative Smart Binder product is to produce and complete the Smart Binder, the project aims to reduce waste mortar, improve cost efficiency, save time, and enhance overall quality and aesthetics The methodology involves data collection through surveys, observations, and analysis of project records, followed by data analysis to derive insights into the effectiveness and impact of the Smart Binder product. The anticipated findings encompass increased cost efficiency, reduced waste mortar, heightened productivity, and improved quality in bricklaying operations. These outcomes hold considerable significance for construction professionals, project managers, and investors, as they furnish evidence-based insights for decision-making and contribute to the advancement of more efficient and sustainable construction practices. The project underscores the importance of stakeholder collaboration, ethical considerations, and adherence to industry standards. The abstracted findings and recommendations serve as valuable insights for the construction industry, encouraging the adoption of innovative technologies and practices to optimize bricklaying processes. Overall, the Smart Binder project represents a notable stride in the construction field, aiming to bolster efficiency and quality by deploying smart technologies and methods, ultimately driving sustainable and cost-effective bricklaying practices in large-scale and medium-scale construction projects.